2022
DOI: 10.1002/aur.2846
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude of low frequency fluctuations during resting state fMRI in autistic children

Abstract: Resting state fMRI (rs-fMRI) provides an excellent platform for examining the amplitude of low frequency fluctuations (ALFF) and fractional amplitude of low frequency fluctuations (fALFF), which are key indices of brain functioning. However, ALFF and fALFF have been used only sporadically to study autism. rs-fMRI data from 69 children (40 autistic, mean age = 8.47 AE 2.20 years; age range: 5.2 to 13.2; and 29 non-autistic, mean age = 9.02 AE 1.97 years; age range 5.9 to 12.9) were obtained from the Autism Brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…The interest in the different resonance magnetic modalities highlights specific brain areas such as the involvement of the ACC, and posterior cingulate cortex (PCC) in ASD symptoms, specifically magnetic resonance spectroscopy which relates cingulated cortices dysfunction to deficits in joint attention and social skills in ASD [13][14][15][16][17][18][19][20][21]. Increasing of these, neuropathology advances [22][23][24][25][26][27], structural MRI [28][29][30][31][32], fMRI [33][34][35][36][37][38][39][40], PET [41,42], and SPECT [43,44], including EEG-evoked potentials [45][46][47][48] indicate the cingulated cortices as one of the most affected areas of the brain responsible for the symptoms of the autism triad mainly [49].…”
Section: Introductionmentioning
confidence: 99%
“…The interest in the different resonance magnetic modalities highlights specific brain areas such as the involvement of the ACC, and posterior cingulate cortex (PCC) in ASD symptoms, specifically magnetic resonance spectroscopy which relates cingulated cortices dysfunction to deficits in joint attention and social skills in ASD [13][14][15][16][17][18][19][20][21]. Increasing of these, neuropathology advances [22][23][24][25][26][27], structural MRI [28][29][30][31][32], fMRI [33][34][35][36][37][38][39][40], PET [41,42], and SPECT [43,44], including EEG-evoked potentials [45][46][47][48] indicate the cingulated cortices as one of the most affected areas of the brain responsible for the symptoms of the autism triad mainly [49].…”
Section: Introductionmentioning
confidence: 99%
“…It is temporally stable (Kublbock et al, 2014) and is considered to be a valid metric for assessing SNA variations associated with neuropsychiatric disorders (Zhou et al, 2010). The study has shown significantly lower ALFF in the left parietal cortex, precuneus, and right insula in ASD (Karavallil Achuthan et al, 2023). Regional homogeneity (ReHo) measures the regional homogeneity of SNA (Kendall, 1990) with high testretest reliability (Zuo & Xing, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…That is, functional concordance had the potential to capture commonalities between different metrics and provided new insights into temporal dynamics for the study of intrinsic brain activity in related disorders. To date, abundant studies on ASD have discovered that ALFF (Karavallil Achuthan et al, 2023), ReHo (Dajani & Uddin, 2016), dALFF, and dReHo (Wu et al, 2022) are altered in multiple brain regions. However, these explorations were performed from a single aspect, and the findings were incompatible.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, resting-state fMRI has been widely used to analyze the differences in spontaneous brain activity and functional connectivity of various brain regions through various measures, including fractional Amplitude of Low-Frequency Fluctuations (fALFF) and Regional Homogeneity (ReHo) ( 16 ). The fALFF is a method for quantifying spontaneous brain activity by measuring the intensity fluctuation of fMRI signals with specific frequencies in a given region of interest ( 17 ). It reflects the synchronization of neuronal oscillations within a region and has been used to investigate various neurological and psychiatric disorders ( 18 ).…”
Section: Introductionmentioning
confidence: 99%